STATUS UTANG KREDITOR SINDIKASI DALAM PERKARA KEPAILITAN DAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG - Abdul Hamid (Fakultas Hukum Universitas Pembangunan Nasional Veteran Jakarta, 2024)
With the development of the economy, the demand for credit from both the public and businesses has increased. However, current regulations limit banks through the Legal Lending Limit (BMPK). The demand for funds often exceeds the BMPK, thus alternatives such as syndicated loans are utilized for large-scale funding. Syndicated loans present different complications in cases of bankruptcy and suspension of debt payment obligations (PKPU), which are closely related to debt matters. This article examines the regulations on syndicated loans in Indonesia and their status in bankruptcy and PKPU cases, using normative research that examines secondary data. Although there is no specific legislation yet, syndicated loans adhere to several regulations, including Law No. 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations, which governs the status of syndicated creditors. Syndicated loan agreements must consider clauses regarding the separation or consolidation of the rights of syndicated creditors).